1993
DOI: 10.1002/hed.2880150305
|View full text |Cite
|
Sign up to set email alerts
|

Immediate free flap mandibular reconstruction: Significance of adequate surgical margins

Abstract: The pathologic records of 182 consecutive patients who had mandible resections were reviewed to determine the incidence of positive margins in the bone specimens and the risk factors associated with positive margins. Of the 182 cases reviewed, 82 (45%) were found to have involvement of the mandible at the time of resection and four (2%) were found to have positive margins. The predominant tumor histology was squamous cell carcinoma, 148 of 182 (81%), followed in frequency by osteosarcoma 12 of 182 (7%), saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…In the early series of segmental resections, the percentage of invaded mandibles tended to be low 22% (23/104) 11 and 30% (3/111) 15 . More up to date series report a much higher rate of mandibular invasion for segmental resection of 65-100% 1,5,[16][17][18][19][20] more consistent with the present study. At present the only method to audit the accuracy of mandibular resection is the margin, and the presence and extent of mandibular invasion.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the early series of segmental resections, the percentage of invaded mandibles tended to be low 22% (23/104) 11 and 30% (3/111) 15 . More up to date series report a much higher rate of mandibular invasion for segmental resection of 65-100% 1,5,[16][17][18][19][20] more consistent with the present study. At present the only method to audit the accuracy of mandibular resection is the margin, and the presence and extent of mandibular invasion.…”
Section: Discussionsupporting
confidence: 94%
“…Previous papers have reported that it is the soft tissue resection, which is the main determinant of compromised margins with compromised bone margins much less likely 14,20,22 . The question of whether a segmental resection of the mandible will ensure a higher chance of a clear soft tissue margin in the presence of early or an uninvaded mandible has not been answered.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of mandible defects result from resection of advanced squamous cell carcinomas (SCC), which involve the mandible by extension from intraoral structures [6]. Several factors complicate the reconstruction of these mandibular defects:…”
Section: Etiology Of Mandible Defectsmentioning
confidence: 99%
“…Historically, segmental mandibular resection left patients significantly disabled, horribly disfigured, and socially isolated due to a lack of reliable reconstructive methods [1]. However, through advances made in reconstructive microsurgery over the last three decades not only have the boundaries of mandibular tumor respectability been extended, but surgeons can now also expect reasonable postoperative functional and aesthetic outcome [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The most common reason for mandibular resection is ablative surgery for large neoplasms involving the mandible, such as ameloblastomas. 1,2 An extensive ameloblastoma sometimes requires segmental mandibular resection or hemimandibulectomy. 3 Reconstruction of these mandibular defects is challenging, and various reconstruction methods are required to achieve functional and esthetic rehabilitation.…”
mentioning
confidence: 99%